Synthesis and HDAC inhibitory activity of pyrimidine-based hydroxamic acids - Jakubkiene, Virginija; Valiulis, Gabrielius Ernis; Schweipert, Markus; Zubriene, Asta; Matulis, Daumantas; Meyer-Almes, Franz-Josef; Tumkevicius, Sigitas (Beilstein Journal of Organic Chemistry, 2022)
Histone deacetylases (HDACs) play an essential role in the transcriptional regulation of cells through the deacetylation of nuclear histone and non-histone proteins and are promising therapeutic targets for the treatment of various diseases. Here, the synthesis of new compounds in which a hydroxamic acid residue is attached to differently substituted pyrimidine rings via a methylene group bridge of varying length as potential HDAC inhibitors is described. The target compounds were obtained by alkylation of 2-(alkylthio)pyrimidin-4(3H)-ones with ethyl 2-bromoethanoate, ethyl 4-bromobutanoate, or methyl 6-bromohexanoate followed by aminolysis of the obtained esters with hydroxylamine. Oxidation of the 2-methylthio group to the methylsulfonyl group and following treatment with amines resulted in the formation of the corresponding 2-amino-substituted derivatives, the ester group of which reacted with hydroxylamine to give the corresponding hydroxamic acids. The synthesized hydroxamic acids were tested as inhibitors of the HDAC4 and HDAC8 isoforms. Among the synthesized pyrimidine-based hydroxamic acids N-hydroxy-6-[6-methyl-2-(methylthio)-5-propylpyrimidin-4-yloxy]hexanamide was found to be the most potent inhibitor of both the HDAC4 and HDAC8 isoforms, with an IC50 of 16.6 µM and 1.2 µM, respectively.
Keywords: alkylation; aminolysis; HDAC inhibitors; hydroxamic acid; pyrimidine